1983
DOI: 10.1126/science.6823563
|View full text |Cite
|
Sign up to set email alerts
|

Action Potentials in Macrophages Derived from Human Monocytes

Abstract: The electrical activity of macrophages derived from human blood monocytes was recorded in vitro with intracellular microelectrodes and was analyzed with computer-assisted data acquisition and analysis techniques. In cells impaled 6 to 8 days after the cultures were prepared, the resting potentials reached a maximum value of -72 millivolts. The cells were electrically excitable; spikes exhibited a slow upstroke, a fast downstroke, a discrete threshold, a large overshoot, and a brief undershoot. Repetitive firin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…5B) -activated K ϩ channels may explain the initial depolarization and subsequent hyperpolarization observed in mouse macrophages (8) and the transient outward current followed by a sustained inward current reported in human alveolar macrophages (10) following Fc␥R activation. Indeed, earlier microelectrode studies reporting action potentials in human monocyte-derived macrophages (25) may also be explained along similar lines.…”
Section: Discussionmentioning
confidence: 77%
“…5B) -activated K ϩ channels may explain the initial depolarization and subsequent hyperpolarization observed in mouse macrophages (8) and the transient outward current followed by a sustained inward current reported in human alveolar macrophages (10) following Fc␥R activation. Indeed, earlier microelectrode studies reporting action potentials in human monocyte-derived macrophages (25) may also be explained along similar lines.…”
Section: Discussionmentioning
confidence: 77%
“…Cultured macrophages derived from human monocytes have an excitable membrane (1) and changes in membrane potential are among the earliest detectable events upon stimulation of phagocytosis (2). So far, direct membrane potential or current measurements have been made with the use of intracellular glass microelectrodes (1,3,4). This type of electrode, however, seriously hampers the study of ionic currents in small cells such as macrophages (3).…”
Section: Introductionmentioning
confidence: 99%
“…Early measurements of Vm were misinterpreted as action potentials (McCann et al, 1983). Values of around -75 mV have been recorded (McCann et al, 1987;Gallin & Sheehy, 1985;Buisman et al, 1988), and it has been suggested that time of adherence is not important because rapid hyperpolarization was observed after only 30 minutes post-adhesion (Gallin & Sheehy, 1985).…”
Section: Macrophage Passive Membrane Propertiesmentioning
confidence: 99%